Taxonomic studies on Lepidocyrtus Bourlet, 1839 (Collembola: Entomobryidae) from India: one new species, one new record, and redescription of two species - Mazumdar, Souvik; Mandal, Pritha; Mandal, Gurupada; Kar, Surajit (Zootaxa, 2026)
This study describes one new species and presents one new record of Lepidocyrtus Bourlet from India, also providing detailed taxonomic accounts for other two members of the genus found in the country. Lepidocyrtus (Cinctocyrtus) cyaneuropygus sp. nov. can easily be distinguished from other species of the subgenus by bluish pigment on the last two abdominal segments, labial triangle formula and chaetotaxy. The new species shares similarities with Lepidocyrtus (Cinctocyrtus) sandakanicus Yoshii in labial triangle chaetae. However, it can be distinguished by differences in chaetotaxy and other morphological characters. Lepidocyrtus (Ascocyrtus) concolourus Nguyen is recorded for the first time from India (Gujarat), and complements to the original description are provided based on current taxonomic standards. Besides, taxonomic notes have been added for two poorly described species, viz., one endemic species from India, Lepidocyrtus (Cinctocyrtus) satkosiaensis Mandal, Suman & Bhattacharya, and the cosmopolitan Lepidocyrtus (Cinctocyrtus) medius Schäffer. An identification key to the Indian species of the subgenus Cinctocyrtus Yoshii & Suhardjono is also provided.